Exercise economy does not change after acclimatization to moderate to very high altitude - Lundby, C.; Calbet, J. A. L.; Sander, M.; van Hall, G.; Mazzeo, R. S.; Stray-Gundersen, J.; Stager, J. M.; Chapman, R. F.; Saltin, B.; Levine, B. D. (Scandinavian Journal of Medicine & Science in Sports, 2007)
For more than 60 years, muscle mechanical efficiency has been thought to remain unchanged with acclimatization to high altitude. However, recent work has suggested that muscle mechanical efficiency may in fact be improved upon return from prolonged exposure to high altitude. The purpose of the present work is to resolve this apparent conflict in the literature. In a collaboration between four research centers, we have included data from independent high-altitude studies performed at varying altitudes and including a total of 153 subjects ranging from sea-level (SL) residents to high-altitude natives, and from sedentary to world-class athletes. In study A (n=109), living for 20-22 h/day at 2500 m combined with training between 1250 and 2800 m caused no differences in running economy at fixed speeds despite low typical error measurements. In study B, SL residents (n=8) sojourning for 8 weeks at 4100 m and residents native to this altitude (n=7) performed cycle ergometer exercise in ambient air and in acute normoxia. Muscle oxygen uptake and mechanical efficiency were unchanged between SL and acclimatization and between the two groups. In study C (n=20), during 21 days of exposure to 4300 m altitude, no changes in systemic or leg VO2 were found during cycle ergometer exercise. However, at the substantially higher altitude of 5260 m decreases in submaximal VO2 were found in nine subjects with acute hypoxic exposure, as well as after 9 weeks of acclimatization. As VO2 was already reduced in acute hypoxia this suggests, at least in this condition, that the reduction is not related to anatomical or physiological adaptations to high altitude but to oxygen lack because of severe hypoxia altering substrate utilization. In conclusion, results from several, independent investigations indicate that exercise economy remains unchanged after acclimatization to high altitude.